Does the association between cognition and education differ between older adults with gradual or rapid trajectories of cognitive decline?. Issue 4 (4th July 2022) - Williams, Benjamin David; Pendleton, Neil; Chandola, Tarani
ABSTRACT: Education is associated with improved baseline cognitive performance in older adults, but the association with maintenance of cognitive function is less clear. Education may be associated with different types of active cognitive reserve in those following different cognitive trajectories. We used data on n = 5642 adults aged >60 from the English Longitudinal Study of Aging (ELSA) over 5 waves (8 years). We used growth mixture models to test if the association between educational attainment and rate of change in verbal fluency or immediate recall varied by latent class trajectory. For recall, 91.5% (n = 5164) of participants were in a gradual decline class and 8.5% (n = 478) in a rapid decline class. For fluency, 90.0% (n = 4907) were in a gradual decline class and 10.0% (n = 561) were in a rapid decline class. Educational attainment was associated with improved baseline performance for both verbal fluency and recall. In the rapidly declining classes, educational attainment was not associated with rate of change for either outcome. In the verbal fluency gradual decline class, education was associated with higher (an additional 0.05–0.38 words per 2 years) or degree level education (an additional 0.04–0.42 words per 2 years) when compared to those with no formal qualifications. We identified no evidence of a protective effect of education against rapid cognitive decline. There was some evidence of active cognitive reserve for verbal fluency but not recall, which may reflect a small degree of domain-specific protection against age-related cognitive decline.